2008
DOI: 10.1002/eji.200737045
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus abrogates IFN‐γ response in respiratory epithelial cells by disruption of the Jak/Stat pathway

Abstract: The innate immunity to viral infections induces a potent antiviral response mediated by interferons (IFN). Although IFN-c is detected during the acute stages of illness in the upper respiratory tract secretions and in the serum of influenza A virus-infected individuals, control of influenza A virus is not dependent upon IFN-c as evidenced by studies using anti-IFN-c Ab and IFN-c -/-mice. Thus, we hypothesized that IFN-c is not critical in host survival because influenza A virus has mechanisms to evade the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 64 publications
1
45
0
2
Order By: Relevance
“…From our results, PAR 2 seems to trigger a signal that counteracts the IAV-mediated inhibitory signal for IFN-␥ release. In line with this hypothesis, it was recently shown that IAV abrogates the IFN-␥ response to evade its antiviral activity (48). Thus, a balance between inhibitory and activating signals could determine the release of IFN-␥ after IAV infection, and full activation of PAR 2 would overcome IAV-induced-inhibition of IFN-␥ release.…”
Section: Discussionmentioning
confidence: 83%
“…From our results, PAR 2 seems to trigger a signal that counteracts the IAV-mediated inhibitory signal for IFN-␥ release. In line with this hypothesis, it was recently shown that IAV abrogates the IFN-␥ response to evade its antiviral activity (48). Thus, a balance between inhibitory and activating signals could determine the release of IFN-␥ after IAV infection, and full activation of PAR 2 would overcome IAV-induced-inhibition of IFN-␥ release.…”
Section: Discussionmentioning
confidence: 83%
“…Influenza virus can infect DCs and other APCs, and alter the cell Ag-processing machinery-for instance, by elevating active cathepsin B levels (39). In this regard, influenza A virus infection of epithelial cells inhibited the IFN-g-induced CIITA, resulting in decreased processing of Ags through the MHC II pathway and altered peptide presentation to CD4 T cells (40). It will be relevant to determine in the future if a similar effect occurs in the DCs of mice infected with mycobacteria and influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…One of the initial consequences during influenza virus infection is the rapid virus-mediated antagonism of the host innate response to avoid the generation of a strong antiviral state (8). This is accomplished by several tactics, such as inhibition of the RIG-I signaling pathway (7,17,19), dysregulation of gene expression (18,23), downregulation of type I and II interferon receptor signaling (20,24,34), inhibition of PKR (12,14) and OAS (14), and modulation of apoptosis (5,13,16,36,38,39). Consequently, on one hand, the 1918 virus antagonizes the innate response, but on the other hand, Mx1 competent animals are able to partially control virus growth.…”
Section: Discussionmentioning
confidence: 99%